(untitled) (The Pakistan Development Review, 2016)
Rising spatial disparities in socioeconomic development is a major concern in developing economies. Regional inequality is a dimension of overall inequality, but it has added significance when spatial and regional divisions align with political and ethnic tensions to undermine social and political stability. This paper is an attempt to document the extent and nature of regional inequality in the level of socioeconomic development. Seventeen indicators related to human resources and standards of living are developed from the district representative household data of Pakistan Social and Living-Standard Measurement (PSLM) survey for the year 2012-13. Development Indicators, for the first time in Pakistan are also aggregated at sub-district level to incorporate the intra-district inequalities in the analysis of spatial disparities. The study provides provincial multidimensional Gini coefficients and district development ranking to evaluate inter and intra provincial disparities respectively in the selected dimensions of socioeconomic development with the help of Inequality-adjusted Socioeconomic Development Index (ISDI). JEL Classification: D63, I31 Keywords: Multidimensional Inequality, Inequality Adjusted Socioeconomic Development Index, Development Ranking, Pakistan